2016
DOI: 10.1007/s11814-016-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Four phase hydrate equilibria of methane and carbon dioxide with heavy hydrate former compounds: Experimental measurements and thermodynamic modeling

Abstract: We experimentally investigated the hydrate dissociation condition for four phase hydrate (H)-aqueous liquid (L Aq )-hydrocarbon rich liquid (L HC )-vapor (V) for the ternary systems of help gas-heavy hydrate former-water. Methane and carbon dioxide are known as help gases and benzene and cyclohexane are considered as heavy hydrate formers. The experimental data were generated using an isochoric pressure-search method. Two different equations of state (EOS) were employed to study the equilibrium phase behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Among various guest materials, methane (CH 4 ) and carbon dioxide (CO 2 ) have attracted the most attention from energy and environmental points of views. , CH 4 can exist as the gas hydrate when CH 4 gas from biogenic or thermogenic origin meets water molecules under natural low-temperature and high-pressure conditions (for example, in permafrost regions and deep-sea sediments). The contents of such natural gas hydrates are estimated to be as large as the total of all other fossil fuels. ,, For organic clathrates, Lee et al reported the formation of CH 4 -loaded HQ clathrate by means of the dry synthesis method and analyzed the samples using spectroscopic measurements .…”
Section: Introductionmentioning
confidence: 99%
“…Among various guest materials, methane (CH 4 ) and carbon dioxide (CO 2 ) have attracted the most attention from energy and environmental points of views. , CH 4 can exist as the gas hydrate when CH 4 gas from biogenic or thermogenic origin meets water molecules under natural low-temperature and high-pressure conditions (for example, in permafrost regions and deep-sea sediments). The contents of such natural gas hydrates are estimated to be as large as the total of all other fossil fuels. ,, For organic clathrates, Lee et al reported the formation of CH 4 -loaded HQ clathrate by means of the dry synthesis method and analyzed the samples using spectroscopic measurements .…”
Section: Introductionmentioning
confidence: 99%
“…However, CPA application for the vapor-liquid equilibria (VLE) (Folas et al 2006) and liquid-liquid equilibria (LLE) (Oliveira et al 2007) of natural gas hydrate composition has been investigated before 2007; Kontogeorgis et al (2007) were the first ones to combine CPA EoS with the vdW-P model and suggested reliable models for the phase behavior of water, alcohols, and natural gas components. Tavasoli et al (2016) investigated the influence of cyclic hydrocarbons (i.e., benzene and cyclohexane) on the methane and CO 2 hydrates. They implemented the fugacitybased model, in which Valderrama-Patel-Teja (VPT) EoS [with non-density-dependent (NDD) mixing rule] (Valderrama 1990) and Statistical Associating Fluid Theory EoS presented by Huang and Radosz (SAFT-HR) Radosz 1990, 1991) were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors influence the hydrate equilibrium calculations including: the hydrate model selection, the appropriate EoS selection, type of hydrate former, existence of inhibitors Fig. 3 Comparison of the experimental data (Sun et al 2002;Tohidi et al 1996;Tavasoli and Feyzi 2016;Danesh et al 1993;Mohammadi et al 2009a;Tavasoli and Feyzi 2016;Mooijer-van den Heuvel et al 2001) and the predictions of SAFT-HR and VPT EoSs (Tavasoli and Feyzi 2016) for the effect of cyclic hydrocarbons on the methane and CO 2 gas hydrates and promoters in the system, and choosing the proper statistical or empirical relations for calculation of the Langmuir constants. In the thermodynamic modeling of hydrate equilibrium conditions, two approaches are used in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Lines: full, this work; dashed, Multiflash results. Data are from Tavasoli and Feyzi (○) and Adisamito et al (Δ).…”
Section: Resultsmentioning
confidence: 99%